Expression of Group I Metabotropic Glutamate Receptors in Rat Hippocampal Cells in Culture and Their Characterization by Intracellular Calcium Ion Dynamics - Yoshitoku Yoshida; Nagisa Matsumoto; Remi Tsuchiya; Mitsuhiro Morita; Hiroyoshi Miyakawa; Yoshihisa Kudo (Elsevier, 2003)
The distribution of group I metabotropic glutamate receptors in rat hippocampal cells in culture was examined by calcium imaging and immunocytochemistry. To distinguish different cell types in the culture, the effects of t-ACPD ((1S,3R)-1-aminocyclopentane-1,3-dicarboxylic acid) and of NMDA (N-methyl-D-aspartate) were examined. About 40% of the cultured cells showed either a transient increase or a sustained or oscillatory increase in the intracellular calcium concentration ([Ca2+]i) during t-ACPD administration, while about 60% of the cells showed a sustained [Ca2+]i increase in response to NMDA. Cells that showed an oscillatory [Ca2+]i change during t-ACPD administration did not respond to NMDA administration, while cells that showed a sustained [Ca2+]i increase during NMDA administration did not show any oscillatory response to t-ACPD. After pharmacological examination using those two agonists, the cultured cells were subjected to immunocytochemistry using anti-GFAP and ant-MAP-2 antibodies to distinguish, respectively, astrocytes and neurons. All cells responding to NMDA with a sustained [Ca2+]i increase were MAP-2-positive, whereas all cells showing either oscillatory or sustained [Ca2+]i increase in response to t-ACPD were GFAP-positive. The present results show that, in these cultures, group I metabotropic glutamate receptors are mainly expressed on glial cells and contribute to dynamic [Ca2+]i changes in astrocytes.